Relation between adenoid size and otitis media with effusion - Skoloudik, L; Kalfert, D; Valenta, T; Chrobok, V (European annals of otorhinolaryngology, head and neck diseases, 2018)
AIMS: This study compares the efficacy of adenoidectomy on otitis media with effusion (OME) in patients with different size of adenoids and the connection between differently sized adenoids and middle ear effusion. MATERIAL AND METHODS: Children with a history of at least 3 months' OME underwent adenoidectomy and myringotomy without the insertion of a tympanostomy tube. Treatment assignment was stratified by adenoids' size causing choanal obstruction (grade I-III) and according to Eustachian tube ostium obstruction (grade A-C). The subjects were followed for 12 months. RESULTS: Adenoidectomy was significantly more effective in children with adenoids in contact with torus tubarius (grade B, C) compared to those with small adenoids without contact (P<0.001). The volume of the adenoids was irrelevant (P=0.146). The size of adenoids did not affect the viscosity of the middle ear secretion. The distribution of mucous and serous secretion was not dependent on the size of adenoids; the efficacy of adenoidectomy was 82% in mucous as well as serous secretion. CONCLUSION: The relation between adenoids and torus tubarius is more important than the volume of the adenoids. The viscosity of middle ear fluids (serous or mucous) did not influence the rate of treatment efficacy.
Keywords: Male; Child, Preschool; adenektomie; Adolescent; následné studie; Child; adenoidy; dítě; mužské pohlaví; Adenoids; hypertrofie; otitis media s výpotkem; mladiství; Follow-Up Studies; předškolní dítě; lidé; ženské pohlaví; Otitis Media with Effusion; Humans; Hypertrophy; Female; Adenoidectomy